Pengaruh Kualitas Produk, Citra Merek dan Harga terhadap Keputusan Pembelian - Nova Ardiyansyah; Suryari Purnama (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research examines and analyzes the influence of product quality, brand image, price simultaneously and partially on purchasing decisions. The research approach used in this research is quantitative research. The sample selection criteria in this study were aged 17-28 years who had purchased packaged tea (Tea Pucuk and Teh Botol) during the last 6 months in the West Jakarta area. The questionnaires collected were 160 respondents, the data was then processed using the multiple linear regression method. Based on the results of the analysis, it is known that the variables product quality, brand image, price simultaneously have a positive effect on purchasing decisions. Partially, the variables product quality, brand image, price have a positive influence on purchasing decisions.